2021
DOI: 10.3389/fvets.2021.595024
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Factors Associated With Caligus rogercresseyi Infection, Abundance, and Spatial Distribution in Southern Chile

Abstract: Sea lice (Caligus rogercresseyi) are external parasites that affect farmed salmonids in Chile, and the scale of their sanitary and economic impact cannot be overstated. Even though space–time patterns suppose parasite aggregation, specific locations related to different infestation levels, as well as their associated factors across the geographic range involved, had not been investigated as of the writing of the present article. The understanding of the effects and factors entailed by the presence of C. rogerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…This study, however, did not consider the marine currents in the analysis. In contrast, Lepe-L opez et al 44 analysed a dataset over a period of 5 years (2012-2016), and reported that among the epidemiological factors associated with the abundance and spatial distribution of C. rogercresseyi in southern Chile there is a spatial structure in specific sites with a higher infection pressure, in addition to the average fish weight, salmon species, chemical control ingredient, latitude, temperature, salinity, and year class category.…”
Section: Factors Affecting the Abundance Of C Rogercresseyimentioning
confidence: 99%
See 1 more Smart Citation
“…This study, however, did not consider the marine currents in the analysis. In contrast, Lepe-L opez et al 44 analysed a dataset over a period of 5 years (2012-2016), and reported that among the epidemiological factors associated with the abundance and spatial distribution of C. rogercresseyi in southern Chile there is a spatial structure in specific sites with a higher infection pressure, in addition to the average fish weight, salmon species, chemical control ingredient, latitude, temperature, salinity, and year class category.…”
Section: Factors Affecting the Abundance Of C Rogercresseyimentioning
confidence: 99%
“…This study, however, did not consider the marine currents in the analysis. In contrast, Lepe‐López et al 44 analysed a dataset over a period of 5 years (2012–2016), and reported that among the epidemiological factors associated with the abundance and spatial distribution of C. rogercresseyi in southern Chile there is a spatial structure in specific sites with a higher infection pressure, in addition to the average fish weight, salmon species, chemical control ingredient, latitude, temperature, salinity, and year class category. Zalcman et al 45 analysed the data set provided by Sernapesca for the period 2011–2017, and confirmed that many of the factors that were identified as influencing lice abundance in the early years remain important drivers of sea lice abundance over the long term.…”
Section: Factors Affecting the Abundance Of C Rogercresseyimentioning
confidence: 99%
“…These parasites are parasitic copepods of the family Caligidae and mainly represented by two genera, Caligus and Lepeophtheirus . Two of the principal ectoparasite of these genera affecting salmon farming are Caligus rogercresseyi in the southern hemisphere and Lepeophtheirus salmonids in the northern hemisphere [ 3 , 4 ]. The harmful effect of these parasites is widely known; they can seriously damage the skin, increase stress, reduce growth, and cause high mortality [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%